If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -21 = 7(x + 9) Reorder the terms: -21 + 4x = 7(x + 9) Reorder the terms: -21 + 4x = 7(9 + x) -21 + 4x = (9 * 7 + x * 7) -21 + 4x = (63 + 7x) Solving -21 + 4x = 63 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -21 + 4x + -7x = 63 + 7x + -7x Combine like terms: 4x + -7x = -3x -21 + -3x = 63 + 7x + -7x Combine like terms: 7x + -7x = 0 -21 + -3x = 63 + 0 -21 + -3x = 63 Add '21' to each side of the equation. -21 + 21 + -3x = 63 + 21 Combine like terms: -21 + 21 = 0 0 + -3x = 63 + 21 -3x = 63 + 21 Combine like terms: 63 + 21 = 84 -3x = 84 Divide each side by '-3'. x = -28 Simplifying x = -28
| 2x+8-22x=-10 | | F(x)-7whenF(x)=3X-2 | | 112=(-16t^2)+64t+48 | | 21/4.2 | | 8x-1/2x | | 2/3*5/8 | | 4x-1=4x-2 | | 1/7•10 | | 2.7x+4=(10+x).7 | | -4k^2+4K-1=0 | | .12x+.8y=40.4 | | -3x+-12+15=6-4x | | 2z+7y=z | | -2.4=6.8(x-0.3) | | 7/8*2/9 | | 1/4k=3(-1/4k=3) | | 100x^2-625=0 | | 8m-4=8-5m-10m | | -2x-5=x+16 | | 3n^2-6=0 | | x-1-x=-1 | | -2(3x+4)-x-6=-5x-2(x+1)+5 | | -2x+12=2x+4 | | 13.2-3.9= | | 4m-m+16=9m+(-30) | | 4y+28y^2=0 | | 4t+2+t=57 | | 3(4x+5)-2=6x+1 | | 3947.2833=1/3*342.25*h | | 87-x=97 | | c/3-3=10 | | 9y+y+3y= |